Chanarin-Dorfman syndrome - (:unkn) unknown (AVES, 2018)
Chanarin Dorfman syndrome is a multisystem, very rare, autosomal recessive lipid storage disorder, characterized by the accumulation of lipid vacuoles in neutrophils, and was first described by Dorfman in 1974. Due to a mutation in the ABHD5 gene of the short arm of chromosome 3, lipid is stored in the granulocytes at various sites in the human body, such as the muscle, liver, eye, ear, central nervous system, and bone marrow. Clinically, the disease is presented with ichthyosis, hearing loss, hepatomegaly, splenomegaly, cirrhosis, cataract, keratopathy, myopathy, and mental retardation. A 38-year-old male patient was referred to our Internal Medicine Clinic for consultation with laboratory findings as follows: high aspartate aminotransferase (AST; 203 U/L), alanine aminotransferase (ALT; 151 U/L), gamma-glutamyl transferase (GGT; 167 U/L), creatine kinase (CK; 1127 U/L) levels and low platelet levels (108000). After ultrasonography and gastroscopy, the patient was diagnosed with liver cirrhosis. Bilateral mixed-type hearing loss on audial tests and bilateral punctuate keratopathy, ectropion, and cataract in the left eye on ophthalmological tests were found. For the definitive diagnosis of Chanarin Dorfman syndrome, peripheral blood was examined, which revealed lipid accumulation in the neutrophils (Jordan's anomaly). We emphasize that if a patient has unusual findings, such as ichthyosis, hearing loss, hepatomegaly, splenomegaly, cirrhosis, cataract, keratopathy, myopathy, and mental retardation, the possibility of Chanarin Dorfman syndrome should be considered.
Keywords: Ichthyosis; fibrosis; cataract; ectropion; hearing loss; lipid droplets